Clinical and microbiological profile of patients with diabetic foot requiring admission to a high complexity hospital. Case Series - Valderrama-Molina, Carlos Oliver; Puerta Gómez, Andrés; Arango Rivas, Ana María; Mejía Arrieta, Daniel; Lopera Restrepo, Juan Camilo; Gómez Roldán, Carlos Ignacio (Revista Colombiana de Ortopedia y Traumatología, 2020)
Background: Infected diabetic foot is a frequent complication of diabetes and a marker of patient deterioration. There is little information in Colombia on the characteristics of patients that enter the highly complex emergency services with this condition and their outcomes, such as amputation and microbiological profile. Materials: Case series of patients admitted to the emergency department of Pablo Tobón Uribe Hospital whose main consultation was infected diabetic foot. The medical records were retrospectively analysed and descriptive statistical tools were used to characterise the population, as well as the variables related to diagnosis, treatment, and early in-hospital outcomes. Results: Between January 2009 and December 2013, 118 patients with 145 ulcers due to an infected diabetic foot were admitted. The HbA1c was > 6.5 in 90%, and 52% had renal dysfunction, 51% with peripheral arterial disease, and 57% had ulcers grade 3 or higher in the Wagner classification. The infection was polymicrobial in 63%, and 58% required amputation, with 62% of amputations being classed as minor. Mortality was 10%, and mortality attributable to diabetic foot infection or complications derived from amputation was 1.7%. Discussion: Patients with diabetic foot admitted to the emergency room of a high complexity hospital in Colombia have an advanced systemic disease,related to renal and peripheral vascular dysfunction, and serious local injuries with advanced bone and joint involvement. Given the severity of these conditions, the prevalence of major amputations may be higher than that reported in the literature. Evidence Level: IV